IMPLEMENTASI STRATEGI PUBLIC RELATIONS LAZADA INDONESIA DALAM MEMBANGUN BRAND TRUST TERHADAP SELLER DAN KONSUMEN - Derivanti, Azizah Des; kamila, shahnaz adisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The development of the current era of globalization has various changes. One of them is in technological progress. Lazada is in the 4th position of e-commerce inIndonesia. Brand Trust is the availability of consumers in relying on the ability of the brand in accordance with the functions that have been shown. This study aims to determine the implementation of Lazada Indonesia's Public Relations Strategy in Building Brand Trust towards Sellers and Consumers. PR Lazada collaborates with the media to provide information about Lazada to build Brand Trust. The methodology used is a descriptive qualitative method by conducting direct interviews with Lazada Indonesia's Public Relations. The results of this research Publication through online media, Events in collaboration with Babyologists to get closer to mothers, News creates news by making press releases, Community Involvement by establishing relationships with communities reaching the target, Inform or image maintaining relationships with the media so that there is a lot of positive news about Lazada, Lobby and nego invites readers to use the Lazada application, Social Responsibility PR Lazada has not implemented sustainable CSR Public Relations Lazada Indonesia applies the programs in building Brand Trust towards Sellers and Consumers.